Retomar a terra: como ser indígena na região metropolitana de Belo Horizonte - Thiago Barbosa de Campos (2019)
The following research focus on the understanding of the recent process promoted by the Indigenous population, called Retomada de Terras (resumption of land) which resulted in the creation of the Naô Xohã Settlement (Aldeia Naô Xohã) at October 2017 in the municipality of São Joaquim de Bicas, located in the Metropolitan Region of Belo Horizonte, state of Minas Gerais. The group consists mainly of natives from the Pataxó Hã-Hã-Hãe and Pataxó ethnicity, originated from government official settlements from the south of Bahia state and other natives from other states and cities. Therefore, the dissertation seeks to express whom these individuals are, their involvement with the settlement´s creation, their sociospatial trajectories, the ways the production of space took place, and what has been the retomada (resumption) so far. In dealing with production of space, this work takes into account the influence of other agents. Such agents includes: the Fundação Nacional do Índio (FUNAI), the Brazilian national agency responsible for the demarcation of indigenous lands; the NGO Teto, responsible for building temporary housing for the village; and the mining company Vale, owner of Córrego do Feijão mine dam, which the recently irruption resulted in the devastation of the river that passes on the shores of the Indian claimed territory. The methodology adopted was based upon ethnography research strategies such as: visits to the village, the register of informal conversations, observation of day-to-day activities of the population, narrative interviews, and production of graphic material.